Internal Ribosome Entry Sites Mediate Cap-Independent Translation of Bmi1 in Nasopharyngeal Carcinoma - Wang, Hongbo; Zhu, Yunjia; Hu, Lijuan; Li, Yangyang; Liu, Guihong; Xia, Tianliang; Xiong, Dan; Luo, Yiling; Liu, Binliu; An, Yu; Li, Manzhi; Huang, Yuehua; et al. (Frontiers in Oncology, 2020)
Bmi1 is overexpressed in multiple human cancers. We previously reported the oncogenic function and the transcription regulation mechanisms of Bmi1 in nasopharyngeal carcinoma (NPC). In this study, we observed that the mRNA and protein levels of Bmi1 were strictly inconsistent in NPC cell lines and cancer tissues. Inhibitors of proteasome and lysosome could not enhance the protein level of Bmi1, indicating that Bmi1 may be post-transcriptionally regulated. IRESite analysis showed that there were two potential internal ribosome entry sites (IRESs) in the 5'-untranslated region (5’-UTR) of Bmi1. Luciferase assay demonstrated that the 5’-UTR of Bmi1 have IRES activity, which may mediate cap-independent translation. The IRES activity of the Bmi1 5’-UTR was significantly reduced after the mutation of the two IRES elements. Taken together, these results suggested that the IRES elements mediating translation is a novel post-transcriptional regulation mechanism of Bmi1.